Inheritance : a luck game which ought to be redefined - Chiang, Madeline Ya Yuen (Nanyang Technological University, 2022)
Our choices and circumstances revolve around an intangible element called luck which governs our lives in more ways than we perceive. Our birthright for one which holds a massive influence on the trajectory of our lives is governed by it. In a world of scarcity, inflation and a rising population, concerns with regards to wealth distributions arise especially among the rising divide of economic inequality. While the common inheritance in the form of wealth is often awarded to the reason for wealth gaps, we should take a closer look at nonfinancial capitals to which the rich possess that help them build their empires. Hence it is the question of morality that arises, is inheritance just and how we should go about equalizing the luck game.